Weakening Participation in A Chain Reaction: Facts on Two Interrelated Decentralization-based Programs - George Towar Ikbal Tawakkal (Universitas Sultan Ageng Tirtayasa, 2023)
Abstract: The debate over whether the concept of decentralization is related to the concepts of democracy, participation, and empowerment has become a topic of interest in the scientific literature. Some scientists argue that there is a link between decentralization and democracy, while others do not. The government expects decentralization to strengthen democracy at the local level. Decentralization has enabled many countries, particularly Indonesia, to improves democracy. Is it true that decentralization and democracy always go hand in hand? By looking at the consequences of decentralization-based programs, this article examines two programs, one of which is a continuation of the other. The two programs are management of the fish auction sites and management of fisherman’s welfare funds, revealing the continuity of community participation, which is now managed by local government. In 2020, a series of in-depth interviews were conducted with administrators of fish auction sites, administrators of fishermen's welfare funds, and fishermen in Pati Regency. The data shows that the design of decentralization has contributed to the weakening of democracy in a chain reaction.